Bidirectional interactions between NOX2‐type NADPH oxidase and the F‐actin cytoskeleton in neuronal growth cones. (25th April 2014) - Munnamalai, Vidhya; Weaver, Cory J.; Weisheit, Corinne E.; Venkatraman, Prahatha; Agim, Zeynep Sena; Quinn, Mark T.; Suter, Daniel M.
Abstract NADPH oxidases are important for neuronal function but detailed subcellular localization studies have not been performed. Here, we provide the first evidence for the presence of functional NADPH oxidase 2 (NOX2)‐type complex in neuronal growth cones and its bidirectional relationship with the actin cytoskeleton. NADPH oxidase inhibition resulted in reduced F‐actin content, retrograde F‐actin flow, and neurite outgrowth. Stimulation of NADPH oxidase via protein kinase C activation increased levels of hydrogen peroxide in the growth cone periphery. The main enzymatic NADPH oxidase subunit NOX2/gp91phox localized to the growth cone plasma membrane and showed little overlap with the regulatory subunit p40phox. p40phox itself exhibited colocalization with filopodial actin bundles. Differential subcellular fractionation revealed preferential association of NOX2/gp91phox and p40phox with the membrane and the cytoskeletal fraction, respectively. When neurite growth was evoked with beads coated with the cell adhesion molecule apCAM, we observed a significant increase in colocalization of p40phox with NOX2/gp91phox at apCAM adhesion sites. Together, these findings suggest a bidirectional functional relationship between NADPH oxidase activity and the actin cytoskeleton in neuronal growth cones, which contributes to the control of neurite outgrowth.<boxed-text content-type="graphic" id="jnc12734-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> We have previously shown that reactive oxygen species (ROS) are critical for actin organization and dynamics in neuronal growth cones as well as neurite outgrowth. Here, we report that the cytosolic subunit p40phox of the NOX2‐type NADPH oxidase complex is partially associated with F‐actin in neuronal growth cones, while ROS produced by this complex regulates F‐actin dynamics and neurite growth. These findings provide evidence for a bidirectional relationship between NADPH oxidase activity and the actin cytoskeleton in neuronal growth cones.